The Place-shaping Continuum: A Theory of Urban Design Process - Carmona, Matthew (Journal of urban design, 2014)
Drawing on empirical research in London, this paper examines how public spaces in the contemporary city are shaped. Together, the 'contexts', 'processes' and 'power relationships' that are revealed represent an integrated framework in the form of a journey through time during which contemporary public space-exemplified in this paper through the case of public space in London-is moulded. Extrapolating to the larger field of urban design, the discussion advances a theory of the urban design process as a place-shaping continuum. This urban design (or place-shaping) process, in all its complexity and variety, has the potential to anchor the field of urban design, offering a core for intellectual enquiry and policy/practice innovation. To situate this, the paper begins with a brief examination of urban design as a subject for investigation.